Properties, processing and applications of gallium nitride and related semiconductors - Edgar, James H. (IEE : INSPEC, 1999)
Annotation Based on its outstanding properties, including a wide energy band gap, high thermal conductivity, and high electron drift velocity, GaN is uniquely suited for many novel devices including solar-blind UV light detectors, high power microwave transistors, and cold cathode electron emitters. This excellent reference covers the basic physical and chemical properties, surveys existing processing technology, and presents summaries of the current state-of-the-art of devices.
Keywords: Gallium nitride.; Light emitting diodes.; Wide gap semiconductors.; Semiconductors -- Materials.; elektronické knihy; electronic books